2018
DOI: 10.1016/j.trci.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The Alzheimer's Prevention Initiative Autosomal‐Dominant Alzheimer's Disease Trial: A study of crenezumab versus placebo in preclinical PSEN1 E280A mutation carriers to evaluate efficacy and safety in the treatment of autosomal‐dominant Alzheimer's disease, including a placebo‐treated noncarrier cohort

Abstract: IntroductionAutosomal-dominant Alzheimer's disease (ADAD) represents a crucial population for identifying prevention strategies that might modify disease course for cognitively unimpaired individuals at high imminent risk for developing symptoms due to Alzheimer's disease (AD), that is, who have “preclinical” AD. Crenezumab is an antiamyloid monoclonal antibody that binds monomeric and aggregated forms of amyloid β, with highest affinity for oligomers; it is in development for early stages of sporadic AD and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
98
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 57 publications
0
98
0
Order By: Relevance
“…One study further reported a significant race by APOE 4 interaction for both CSF t-tau and p-tau, 12 suggesting that the racial disparities in these biomarkers, and hence in the more downstream clinical changes, may depend on APOE 4 status, consistent with our current findings. Specifically, both biomarker studies 11,12 Inherited Alzheimer Network (DIAN) trials, 33 and the Alzheimer's Prevention Initiative (API) trial 34 are ongoing. Primary prevention trials are currently planned.…”
Section: Discussionmentioning
confidence: 99%
“…One study further reported a significant race by APOE 4 interaction for both CSF t-tau and p-tau, 12 suggesting that the racial disparities in these biomarkers, and hence in the more downstream clinical changes, may depend on APOE 4 status, consistent with our current findings. Specifically, both biomarker studies 11,12 Inherited Alzheimer Network (DIAN) trials, 33 and the Alzheimer's Prevention Initiative (API) trial 34 are ongoing. Primary prevention trials are currently planned.…”
Section: Discussionmentioning
confidence: 99%
“…Over 1,800 Colombian PSEN1 E280A carriers and 4,000 non-carrier family members who trace their lineage back to a single-common ancestor with the mutation participate in research at the University of Antioquia and collaborating sites in the United States [11]. As research in this cohort progresses – including a five-year phase 2 clinical trial of the anti-amyloid agent Crenezumab involving 300 Colombian kindred members, 200 of whom are mutation carriers [12] – a review that unifies our understanding of the PSEN1 E280A literature is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The Alzheimer's Prevention Initiative (API), established in 2010, is a collaborative research program led by Banner Alzheimer's Institute in partnership with other key organizations working to accelerate the evaluation of interventions to prevent AD dementia [4,8]. In 2012, API received a National Institutes of Health (NIH) grant to help support the Colombia Autosomal Dominant AD Trial (ctgov:NCT01998841), the first funded prevention trial of an investigational disease‐modifying treatment in cognitively unimpaired mutation carriers and noncarriers from the world's largest autosomal dominant AD kindred.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, API received a National Institutes of Health (NIH) grant to help support the Colombia Autosomal Dominant AD Trial (ctgov:NCT01998841), the first funded prevention trial of an investigational disease‐modifying treatment in cognitively unimpaired mutation carriers and noncarriers from the world's largest autosomal dominant AD kindred. Because many kindred members do not want to know their genetic status and there was no established paradigm for genetic disclosure in Colombia, this ongoing study includes both mutation carriers who are randomized to active treatment or placebo and noncarriers who receive placebo, and it does not include genetic disclosure [4].…”
Section: Introductionmentioning
confidence: 99%